TORSION OF A WANDERING SPLEEN (a case report) - S.R, , Baymakov (International Journal of Psychosocial Rehabilitation, 2020)
Introduction. Splenic dystopia, or a wandering spleen, is a rare and unusual case which is represented by movability of the spleen from its normal left hypochodrical position to other pelvic cavities. It appears as a result of many factors such as congenital insufficiency of the ligamentous apparatus, atypical location and elongation of its vascular pedicle. But the laxity of the spleen’s primary supporting ligaments is considered to be the most agreed-upon factor. This rare pathology affects mainly young adults, particularly women and children, which presents as an asymptomatic abdominal mass or abdominal discomfort due to the torsion of the pedicle. Clinical manifestations are presented as asymptomatic up to abdominal emergency. Treatment is mostly surgical. The aim of this work is to present and analyze the anamnesis and the treatment of the case. Presentation of case: A case report of splenic torsion from the surgical department of the 3-clinic of the Tashkent Medical Academy is described in the present work. This is a 20 year-old lady with complaints for pain in the left hypochondrium, nausea, dry mouth, forced position due to the pain and general weakness. The patient underwent the following studies: an irrigoscopy – for the Hirschsprung’s disease, MSCT of the abdominal cavity, laparoscopic splenectomy. Surgery “Laparotomy. Splenectomy. Drainage of the abdominal cavity” was performed. Review of literature was made using the keyword combination: “splenic torsion”. Discussion: A splenic torsion is either congenital or acquired. Laparoscopic approach is the preferred surgical intervention. Conclusion: The diagnosis of splenic torsion is very rare, extremely difficult to establish and is clinically nonspecific, especially in patients presenting with acute abdomen. An early diagnosis and surgical care are required for preserving the spleen. Additional imaging examinations (ultrasonic scan and CT) are predominant and can help establish a correct diagnosis, before development of life-threatening complications. Surgery is often necessary and Plenectomy is preferable.